Analysis Of Strategies For Changing Negative Personal Images Into Positive Images On Celebgrams - Prawesti, Prawesti; Azhar, Andi (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
The title of this research is Analysis of Strategies for Changing Negative Personal Images into Positive Images on Celebrities. This research is based on strategies for changing negative images into positive ones on celebgrams in the context of digital marketing. This is important because celebs have a big role in influencing consumer behavior on social media. This research aims to identify effective celebrity strategies on social media, their impact on reputation, career and influence on their followers, as well as the role of management in the business industry.The objects of this research are Jefri Nichol and Rachel Vennya, the research method used is descriptive qualitative methods. The data collection method in this research uses observation, which is carried out by observing posts from Instagram accounts and news articles on social media.By using observation techniques. The results of this research can be concluded that the post-case experiences and personal transformation experienced by two well-known Indonesian celebrities, namely Jefri Nichol and Rachel Vennya, after being involved in a controversy affected their image and careers. The findings show that despite facing huge challenges in maintaining their reputation and existence in the world of entertainment, both of them managed to maintain their popularity and credibility with different approaches.